PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI SURVEY FAKULTAS DENGAN METODE MODEL VIEW CONTROLLER (MVC) DI UNIVERSITAS DHYANA PURA - Mrs Megawati; Gerson Feoh; I Wayan Supriana (LPPM Universitas Dhyana Pura, 2017)
ABSTRACT In this era of globalization is going very fast. Information systems have become a necessityin all aspects of life. Not only that, today information technology has even become the backbone ofhuman life in the provision and provision of information. Through the internet is very helpful toprovide ideas for writers to create a campus website that can provide information for the visitors. At Dhyana Pura University as part of the community in Bali which organizes educationalactivities as a form of care and service to others in order to liberate people from ignorance,backwardness, alienation, and poverty. The information presented at Dhyana Pura University is a lotof one of the Faculty's information. In the design built there will be an addition to the studentsatisfaction survey. At Dhyana University Pura has two Faculties namely, Faculty of Economics &Humanities and Faculty of Health Sciences, Science, and Technology. For prospective students canchoose which faculty will be taken.Keywords - Dhyana Pura University, Information System, PHP And MySQL, Website, Model ViewController. ABSTRAK Di era globalisasi saat ini berlangsung sangat cepat. Sistem informasi sudah menjadi sebuahkeharusan dalam segala aspek kehidupan. Tak hanya itu, saat ini teknologi informasi bahkan telahmenjadi tulang punggung kehidupan manusia dalam penyediaan dan pemberian informasi. Melalui internet tersebut sangat membantu memberikan ide bagi penulis untuk membuat suatu website kampusyang bisa memberikan informasi bagi para pengunjungnya. Di Universitas Dhyana Pura ini sebagai bagian dari masyarakat di Bali yangmenyelenggarakan kegiatan pendidikan sebagai bentuk kepedulian dan pelayanan kepada sesamadengan tujuan untuk membebaskan masyarakat dari kebodohan, keterbelakangan, keterasingan, dankemiskinan. Informasi yang disajikan di Universitas Dhyana Pura ini banyak sekali salah satunyainformasi Fakultas. Pada rancangan yang dibangun akan ada penambahan untuk survey kepuasanmahasiswa. Di Universitas Dhyana Pura memiliki dua Fakultas yaitu, Fakultas Ekonomika &Humaniora dan Fakultas Ilmu Kesehatan, Sains, dan Teknologi. Bagi calon mahasiswa dapat memilihFakultas mana yang akan diambil. Kata Kunci – Universitas Dhyana Pura, Sistem Informasi, PHP Dan MySQL, Website, Model ViewController.